2008
DOI: 10.1080/02640410701591417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exercise on executive processing, short-term and long-term memory

Abstract: In the present study, we evaluated the effects of a brief bout of exercise on executive function, short-term memory, and long-term memory tests. Eighteen young adults (mean age 22.2 years, s = 1.6) performed a set-switching test, a Brown-Peterson test, and a free-recall memory test before and after 40 min of moderate aerobic exercise on a cycle ergometer, and two control conditions. Exercise did not facilitate set switching or short-term memory, which suggests that exercise-induced arousal does not influence e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
173
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(197 citation statements)
references
References 60 publications
15
173
2
3
Order By: Relevance
“…It is not clear why exercise should have differential effects on the four measures of academic performance. Coles and Tomporowski (2008) provided some distinction in respect to the effects of acute bouts of exercise on cognition and proposed that exercise does not influence working memory processes that involve organisation and sequencing of mental operations but can facilitate the consolidation of delayed long-term memories. This distinction is, however, unable to account for the present data as memory for letter positions and wordphoneme associations is already encoded pre-study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear why exercise should have differential effects on the four measures of academic performance. Coles and Tomporowski (2008) provided some distinction in respect to the effects of acute bouts of exercise on cognition and proposed that exercise does not influence working memory processes that involve organisation and sequencing of mental operations but can facilitate the consolidation of delayed long-term memories. This distinction is, however, unable to account for the present data as memory for letter positions and wordphoneme associations is already encoded pre-study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of exercise on adult cognition has been extensively researched (for reviews see Lambourne & Tomporowski, 2010;Tomporowski, 2003), with cognitive performance assessed during exercise (McMorris & Graydon, 1996), following acute exercise (Coles & Tomporowski, 2008;Hopkins, Davis, & Vantieghem, 2012;Tomporowski, et al, 2005), and following long-term exercise exposure (e.g. Castelli, Hillman, Buck & Erwin, 2007;Hopkins et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a meta-analysis by Chang, Labban, Gapin, and Etnier (2012) showed that acute bouts of exercise can have beneficial effects on cognitive tasks executed during, immediately after, or after a delay following the exercise. Short bouts of exercise affect cognitive processes by increasing response speed and accuracy (Tomporowski, 2003), improving working memory capacity (Pontifex, Hillman, Fernhall, Thompson, & Valentini, 2009), as well as improved performance on free-recall tasks (Coles & Tomporowski, 2008). For example, Drollette et al (2014) showed that, after 20 minutes of treadmill walking, preadolescent children had better performance on cognitive tasks gauging attention and inhibitory control compared with children who remained seated.…”
Section: Effects Of Whole-body Movementsmentioning
confidence: 99%
“…However, the relationship between physical exercise and neurocognitive function in young adults is less clear. Acutely, physical exercise seems to have little effect on memory and cognition; executive function processes involved in working memory remain unaltered, although aspects of delayed long-term memory do improve (Coles and Tomporowski, 2008;Tomporowski, 2003). Long-term physical exercise appears to have a slight effect on reaction time in young people (Sherwood and Selder, 1979).…”
Section: Association Between Physical Inactivity and Impaired Cognitimentioning
confidence: 99%